2021
DOI: 10.3389/fgene.2021.653474
|View full text |Cite
|
Sign up to set email alerts
|

Identifying ceRNA Networks Associated With the Susceptibility and Persistence of Atrial Fibrillation Through Weighted Gene Co-Expression Network Analysis

Abstract: Background: Atrial fibrillation (AF) is the most common arrhythmia. We aimed to construct competing endogenous RNA (ceRNA) networks associated with the susceptibility and persistence of AF by applying the weighted gene co-expression network analysis (WGCNA) and prioritize key genes using the random walk with restart on multiplex networks (RWR-M) algorithm.Methods: RNA sequencing results from 235 left atrial appendage samples were downloaded from the GEO database. The top 5,000 lncRNAs/mRNAs with the highest va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Considering the CD8A and CD4 gene markers, as well as a high number of TCR clonotypes, it is plausible that IRF4 is associated with an intensified T-cell response, leading to cardiac damage. In this line, IRF4 exhibits correlations with LINC00964 and LINC00528, both of which have already been implicated in heart diseases (47,48). MIAT, a lncRNA previously linked to CCC (13) and present in our network, is also overexpressed in CCC6 patient.…”
Section: Discussionmentioning
confidence: 67%
“…Considering the CD8A and CD4 gene markers, as well as a high number of TCR clonotypes, it is plausible that IRF4 is associated with an intensified T-cell response, leading to cardiac damage. In this line, IRF4 exhibits correlations with LINC00964 and LINC00528, both of which have already been implicated in heart diseases (47,48). MIAT, a lncRNA previously linked to CCC (13) and present in our network, is also overexpressed in CCC6 patient.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, an increasing number of reports indicate that lncRNAs can regulate protein-coding genes in mammals through the ceRNA network ( 27 ), where lncRNAs function as miRNA sponges to upregulate the expression of their targets ( 28 ). For instance, Liu et al identified LINC00964 as a key lncRNA in AF susceptibility- and persistence-associated ceRNA networks ( 29 ). By integrating three microarray datasets and construction of a ceRNA network, the study by Wu et al discovered that HCG11, KRBOX1-AS1, ACBD5 and RAD52 may compete with WEE1 for has-miR-17-5p to affect the development of AF ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…ceRNAs act as key mediators in the progression of different types of cancer[ 46 ]. Although the ceRNA network has been established in HCC, other novel ceRNA mechanisms need to be elucidated[ 47 - 50 ].…”
Section: Discussionmentioning
confidence: 99%